A gestão dos recursos financeiros do SUS em um município da Bahia - Rosa, Márcia Reis Rocha (2008)
The object of this paper was the process of financial management that to be in focus on the flow of financial resources since the origin as far as the immediate results of health activities. The objective, here, was to analyze municipal management of financial resources of Unified National Health System (SUS). This paper is a single study case that obtained in the documental analyses the evidence sources. The date financial were collected and analyzed through of the four table s proposal by National Health Accounts (NHA) and compared with the documental date. The characteristics of the service provider and of the activities were detailed carefully because of the methodology powerful with high the date separation. The result of research showed profile of date municipal resource: the federal government contributed to 82% of incomes, after municipality contributed to 17%, and, less participation the state that contributed to 1% of incomes. To point the Total Income of R$ 608,5 per capita and the pantry per capita of the 16 unities of the PSF (Family Health Program) vary from R$ 465,4 to R$ 62,3 per capita/unity/year. The Public Pantry with Health (GPS) per capita was R$ 261/hab/year. The PIB per cent that corresponded GPS was 4,4%. The proportion of incomes allocated to the hospitals was 47%, and ambulatory unities 44% showing a different profile of the another municipalities studied. The activities carried by Family Health Program Unities in 2005 were predominant Actions executed by nurse profession (38%); Actions basic medicines (28%) and Actions basic dentist (19%). Conclusion: a low capacity of collection taxes in 2005 year and co-financial insufficient of State. About health financial management of municipal system realized a planning process occurring in parallel; little coincide of LOA and PMS aims; a mask budget execution. The health responsibilities were carried partial proper sub-financial of three government sphere and the financing the federal government totally linked, taking the municipally co-finance what was prioritized by Union, and however, do not remain self municipal incomes to invest in local priorities.